Thermal behavior and cyclic fatigue resistance of three contemporary NiTi heat-treated single-file systems: metallurgical study - Loai Alsofi; Mazen Al-Marshadi; Tariq AbuHaimed; Mey Al-Habib; Rajab Saif; Sarah Bukhari; Mohammed Howait (BMC Oral Health)
Abstract Background This study aims to determine phase transformation temperatures of EndoSequence Reciprocating System (ESR), Wave One Gold (WOG), and Reciproc Blue (RB) via differential scanning calorimetry (DSC). Further, to evaluate the cyclic fatigue behaviors by applying static (SF) and dynamic fatigue (DF) tests. Methods All files’ systems were evaluated using DSC (Netzch 200 F3, Germany) with scans ranging from 80°C to -80°C to compare phase transformation. Twenty files from each file system (n = 20) were tested by cyclic fatigue in SF (n = 10) and in DF (n = 10) and the number of cycles to failure (NCF) was calculated for all groups. The files were rotated in a clockwise motion in a metal tube at 350rpm. The NCF was calculated by multiplying the time until fracture in minutes by speed (350 rpm). The NCF was analyzed statistically using a One-Way Analysis of Variance (ANOVA) to determine if there were significant differences among the experimental groups. Results All files exhibited a single peak in the cooling curve marking martensitic transformation with RB showing martensitic transformation start temperature at around 37oC . ESR and WOG exhibited single endothermic peaks marking austenitic transformation. RB exhibited two endothermic peaks marking R-phase and austenitic transformations. In cyclic fatigue testing, WOG presented the lowest NCF in DF testing compared to ESR and RB (p < .05) with a nonsignificant difference between the latter two. In the SF, ESR showed a statistically significant larger NCF compared to RB, which also showed statistically significant larger NCF compared to WOG (p < .05). Conclusions RB shows martensite transformation start temperature close to body temperature. RB and ESR show improved cyclic fatigue resistance compared to WOG in the SF mode. In the DF mode, WOG showed the lowest cyclic fatigue resistance.